Novel approaches for left atrial pressure relief: Device-based monitoring and management in heart failure - Miyagi, Chihiro; Kuroda, Taiyo; Karimov, Jamshid H.; Fukamachi, Kiyotaka (Frontiers in Cardiovascular Medicine, 2022)
The importance of the left atrium (LA) has been emphasized in recent years as the features of heart failure (HF), especially with regard to variability in patient and pathology phenotypes, continue to be uncovered. Of note, among the population with HF with preserved ejection fraction (HFpEF), pressure or size of the LA have become a target for advanced monitoring and a therapeutic approach. In the case of diastolic dysfunction or pulmonary hypertension, which are often observed in patients with HFpEF, a conventional approach with clinical symptoms and physical signs of decompensation turned out to have a poor correlation with LA pressure. Therefore, to optimize HF treatment for these populations, several devices that are applied directly to the LA have been developed. First, two LA pressure (LAP) sensors (Heart POD and V-LAP Device) were developed and may enable patient self-management remotely with LAP-guided and physician-directed style. Second, there are device-based approaches that aim to decompress the LA directly. These include: (1) interatrial shunt devices; (2) left ventricular assist devices with LA cannulation; and (3) the left atrial assist device. While these novel device-based therapies are not yet commercially available, there is expected to be a rise in the proposition and adoption of a wider range of choices for monitoring or treating LA using device-based options, based on LA dimensional reduction and optimization of the clinically significant pressure relief. Further development and evaluation are necessary to establish a more favorable management strategy for HF.